A commentary on: 'Divergence in floral scent and morphology, but not thermogenic traits, associated with pollinator shift in two brood-site-mimicking Typhonium (Araceae) species'. (28th June 2021) - Rands, Sean A
Abstract : This article comments on: Thomas D. J. Sayers, Kim L. Johnson, Martin J. Steinbauer, Kevin Farnier and Rebecca E. Miller and Divergence in floral scent and morphology, but not thermogenic traits, associated with pollinator shift in two brood-site-mimicking Typhonium (Araceae) species, Annals of Botany, Volume 128, Issue 3, 26 August 2021, Pages 261–260, https://doi.org/10.1093/aob/mcab044